What Factors Influence Farmer's Behavior in Adopting Integrated Pest Management Practices in Mountains of Nepal? - Anisha Sapkota; Kishor Atreya; Subodh Khanal; Kanchan Kattel (AgroEnvironmental Sustainability)
Farmers who have attended the season-long integrated pest management-farmers’ field school (IPM-FFS) are more likely to adopt IPM practices but significant knowledge gaps persist regarding the extent of IPM adoption among farmers in Nepal and the factors influencing their practices. This study thus looks at factors influencing farmers' decisions to adopt IPM practices in Kavrepalanchok district of Nepal. It focuses on six components of the health belief model (HBM): benefits, severity, susceptibility, barriers, self-efficacy, and cues to action. We interviewed both IPM-FFS-trained and other non-trained farmers. Poisson's regression and bootstrapping were used to analyze the relationship between HBM components (independent variables) and the adoption of IPM practices (dependent variable). The analysis was done separately for "IPM-FFS farmers," "other farmers," and both groups combined. Findings show increased adoption of IPM practices by the IPM-FFS trained farmers, driven mainly by the benefits (IRR 1.32, p<0.01). However, HBM components did not show a substantial impact on enhancing the adoption of IPM practices among "other farmers." When combined, perceived benefits (IRR 1.35, p<0.01), self-efficacy (IRR 1.41, p < 0.01), and cues to action (IRR 1.34, p<0.01) significantly enhanced the adoption of greater IPM practices. Findings are similar between normal and bootstrap Poisson regressions. This study shows the importance of improving farmers' confidence through targeted training programs in promoting sustainable agricultural practices.